China's diversifying demand for housing for the elderly. Issue 2 (6th June 2016) - Jia, Min; Heath, Timothy
Abstract : Purpose: This paper aims to examine the trends among the elderly population in China about residential preferences and policy applications, as the elderly is a rapidly expanding demographic group that has increasing and diversifying inclinations for demanding the residential facilities for the elderly (RFEs) now and in the foreseeable future. Design/methodology/approach: Based on a review of the existing literature and policies, a model is conceptualised for understanding the demands of the elderly. Their needs for functional supportiveness and richness of residential resources in RFEs are then categorised into focal groups. Findings: The Chinese elderly's demand for specialised residential facilities is under a shift from seeking deficit relief to pursuing personal choices. It is suggested that there will be a continuing demand for affordable RFEs from a number of key focal groups, including: the functionally impaired; marginally housed; socially isolated; and the elderly requiring social relief. In addition, retirement housing in China is likely to be more affordable for the next elderly generation. However, the immature social welfare system and low average income level of the current elderly generation means that the Chinese Government has tough decisions to make about service priorities. Practical implications: Policy and investment priorities may have to be inclusive of those who demand social relief (free-of-charge) and affordable professional long-term care in RFEs, whereas the rest of the demand could be released by growth in the development of community- and home-based service systems. Originality/value: This study is one of the first to identify the diversifying demands of age-exclusive living facilities for the elderly that deserve priorities in China. The results can inform and guide future policy and project investment in China.